Human cyclooxygenase-1 activity and its responses to COX inhibitors are allosterically regulated by nonsubstrate fatty acids - Zou, Hechang (The American Society for Biochemistry and Molecular Biology, 2012)
Recombinant human prostaglandin endoperoxide H synthase-1 (huPGHS-1) was characterized. huPGHS-1 has a single high-affinity heme binding site per dimer and exhibits maximal cyclooxygenase (COX) activity with one heme per dimer. Thus, huPGHS-1 functions as a conformational heterodimer having a catalytic monomer (E(cat)) with a bound heme and an allosteric monomer (E(allo)) lacking heme. The enzyme is modestly inhibited by common FAs including palmitic, stearic, and oleic acids that are not COX substrates. Studies of arachidonic acid (AA) substrate turnover at high enzyme-to-substrate ratios indicate that nonsubstrate FAs bind the COX site of E(allo) to modulate the properties of E(cat). Nonsubstrate FAs slightly inhibit huPGHS-1 but stimulate huPGHS-2, thereby augmenting AA oxygenation by PGHS-2 relative to PGHS-1. Nonsubstrate FAs potentiate the inhibition of huPGHS-1 activity by time-dependent COX inhibitors, including aspirin, all of which bind E(cat). Surprisingly, preincubating huPGHS-1 with nonsubstrate FAs in combination with ibuprofen, which by itself is a time-independent inhibitor, causes a short-lived, time-dependent inhibition of huPGHS-1. Thus, in general, having a FA bound to E(allo) stabilizes time-dependently inhibited conformations of E(cat). We speculate that having an FA bound to E(allo) also stabilizes E(cat) conformers during catalysis, enabling half of sites of COX activity.